A randomized, double-blind, phase III trial of personalized peptide vaccination for recurrent glioblastoma. Issue 3 (30th November 2018) - Narita, Yoshitaka; Arakawa, Yoshiki; Yamasaki, Fumiyuki; Nishikawa, Ryo; Aoki, Tomokazu; Kanamori, Masayuki; Nagane, Motoo; Kumabe, Toshihiro; Hirose, Yuichi; Ichikawa, Tomotsugu; Kobayashi, Hiroyuki; Fujimaki, Takamitsu; et al.
Abstract: Background: We conducted a phase III trial of personalized peptide vaccination (PPV) for human leukocyte antigen (HLA)-A24+ recurrent glioblastoma to develop a new treatment modality. Methods: We randomly assigned 88 recurrent glioblastoma patients to receive PPV ( n = 58) or the placebo ( n = 30) at a 2-to-1 ratio. Four of 12 warehouse peptides selected based on preexisting peptide-specific immunoglobulin G levels or the corresponding placebos were injected 1×/week for 12 weeks. Results: Our trial met neither the primary (overall survival [OS]) nor secondary endpoints. Unfavorable factors for OS of 58 PPV patients compared with 30 placebo patients were SART2-93 peptide selection ( n = 13 vs 8, hazard ratio [HR]: 15.9), ≥70 years old (4 vs 4, 7.87), >70 kg body weight (10 vs 7, 4.11), and performance status (PS)3 (8 vs 2, 2.82), respectively. Consequently, the median OS for PPV patients without SART2-93 selection plus one of these 3 favorable factors (<70 y old, ≤70 kg, or PS0–2) was significantly longer than that for the corresponding placebo patients (HR: 0.49, 0.44, and 0.51), respectively. Preexisting immunity against both all 12 warehouse peptides besides SART2-93 and the other cytotoxic T lymphocyte epitope peptides was significantly depressed in the patients with SART2-93 selection ( n = 21) compared with that of the patients without SART2-93 selection ( n = 67). Biomarkers correlative for favorable OS of the PPV patients were a lower percentage of CD11b+CD14+HLA-DR low immunosuppressive monocytes and a higher percentage of CD4+CD45RA− activated T cells, the intermediate levels of chemokine C-C ligand 2 (CCL2), vascular endothelial growth factor, interleukin (IL)-6, IL-17, or haptoglobin, respectively. Conclusion: This phase III trial met neither the primary nor secondary endpoints.